Chapter 3 Mnemonic Affordances of Family Photographs Assembling Memorability of Displacement and Soviet Repression - Savolainen, Ulla (Taylor & Francis, 2023)
This chapter contributes to the discussions on memorability by applying assemblage theoretical thinking to the analysis of memory and by developing the notion of mnemonic affordance. It analyzes Ella Ojala's family photographs' affordances in the mediation of the memory of forced migrations and family's dispersal on multiple scales. First, the chapter explores the photographs' affordances in mediating memory of dispersed family. Second, it examines the album's affordances in mediating Ojala's life story in her memoir novels. Third, by contextualizing Ojala's literary works vis-à-vis the time of their publication at the turn of 1990s Finland and discussing their recent archiving, the chapter discusses affordances of the family album in mediation of the memory related to Ingrian Finns' experiences more generally. The chapter indicates some of the potentials of assemblage thinking for conceptualizing memory as processual, malleable, and contingent on various discursive-material and contextual circumstances.